Strategi Station Rotation untuk Meningkatkan Keterampilan 6C Peserta Didik pada Mata Pelajaran Dasar-Dasar Kimia Analisis - Wulaningrum Wulaningrum (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The advancement of science and technology in the twenty-first century necessitates that people have skills applicable to the workplace in addition to academic proficiency. Often called the "6Cs," these 21st-century competencies include collaboration, critical thinking, communication, culture, creativity, and connectivity. 36 students in class X Concentration of Laboratory Testing Analysis (APL) Expertise participated in two cycles of the study's qualitative application of McTaggart's and Kemmis Classroom Action Research (CAR) model. Tests, observations, product evaluations, and group reflections were used to gather data, which was then statistically, descriptively, and qualitatively assessed. The study's findings demonstrated a notable improvement in 6C skills from the adequate category (average 3.01) in cycle I to good (average 3.38) in cycle II, with the critical thinking and communication components showing the largest increase of 0.52 points. Classical learning completeness reached more than 95%, and the quality of products in the form of infographics improved in terms of creativity and conceptual understanding. The results of this study report that the implementation of the station rotation learning model effectively increases 6C skills and creates active, collaborative, and contextual learning in vocational schools.